Highly efficient removal of hexavalent chromium in aqueous solutions via chemical reduction of plate-like micro/nanostructured zero valent iron. Issue 88 (11th December 2017) - Kang, Shenghong; Wang, Guozhong; Zhao, Huijun; Cai, Weiping
Abstract : The plate-like micro/nanostructured zero valent iron has exhibited the significantly enhanced ability to remove Cr(vi ) from the real electroplating wastewater compared with the commercial zero valent iron. Abstract : The removal of hexavalent chromium [Cr(vi )] from aqueous solutions using plate-like micro/nanostructured zero valent iron (MNZVI), which is fabricated in mass production by ball-milling of reductive iron powders, is investigated in this study. It has been shown that this plate-like MNZVI has significantly enhanced ability to remove Cr(vi ) from aqueous solutions as compared to commercial zero valent iron (CZVI). Cr(vi ) in a concentration of 100 ppm at pH = 2 can be removed nearly completely within 20 min by the addition of 1.5 g L −1 MNZVI. The time-dependent removal amount of Cr(vi ) can be well described by a pseudo first-order kinetic model. The reaction rate constant for MNZVI is 20 times larger than that for CZVI. Further experiments have revealed that the Cr(vi ) removal is also associated with the pH value and initial concentration of Cr(vi ) in the solution, in addition to the iron dosage. These enhanced removal performances are attributed to the iron-induced reduction process of Cr(vi ) and the high specific surface area of MNZVI. Further, electroplating wastewater was used to demonstrate the practical applications of MNZVI. The removal capacity is up to 330 mg g −1 in the electroplating wastewater with a 556 ppm initial Cr(vi ) content, which is more than 3 times higher than that of CZVI and also much higher than the previously reported results. This study has demonstrated that the ball milling-induced plate-like MNZVI is a good candidate material for efficient treatment of Cr(vi )-containing wastewater.